Answer:
Pies=$0.85
Donuts= $1.20
Step-by-step explanation:
In the equation let p stand for the number of pies and d stand for the number of donuts.
To solve this set up 2 equations, one representing bill and the other representing Mary Ann.
- Bill's equation is 5p+7d=$12.65.
- Mary Ann's equation is 6p+6d=$12.30
Then solve using a system of equations. Systems of equations can be solved using elimination or substitution. I will use substitution. Solve bill's equation for p. This gives you
. Then, you can substitute that into Mary Ann's equation. This looks like
. Solve for d. Once you solve d=1.20. Finally, substitute 1.20 back into either Bill's or Mary Ann's for d and solve for p. No matter which equation you use p=0.85.
Answer:
b and c
Step-by-step explanation:
It should be $92.00
80 • .15 = 12
so 15% of the total ($80) is 12.
add the 12 to the total 80+12= $92
Answer:
(a): <u>x</u><u> </u><u>is</u><u> </u><u>3</u><u> </u><u>and</u><u> </u><u>ky</u><u> </u><u>is</u><u> </u><u>-</u><u>1</u>
<u>(</u><u>b</u><u>)</u><u>:</u><u> </u><u>k</u><u> </u><u>is</u><u> </u><u>-</u><u>2</u>
Step-by-step explanation:
Let: 3x + ky = 8 be <em>e</em><em>q</em><em>u</em><em>a</em><em>t</em><em>i</em><em>o</em><em>n</em><em> </em><em>(</em><em>a</em><em>)</em>
x - 2 ky = 5 be <em>e</em><em>q</em><em>u</em><em>a</em><em>t</em><em>i</em><em>o</em><em>n</em><em> </em><em>(</em><em>b</em><em>)</em>
<em> </em>Then multiply <em>e</em><em>q</em><em>u</em><em>a</em><em>t</em><em>i</em><em>o</em><em>n</em><em> </em><em>(</em><em>a</em><em>)</em><em> </em>by 2:
→ 6x + 2ky = 16, let it be <em>e</em><em>q</em><em>u</em><em>a</em><em>t</em><em>i</em><em>o</em><em>n</em><em> </em><em>(</em><em>c</em><em>)</em>
Then <em>e</em><em>q</em><em>u</em><em>a</em><em>t</em><em>i</em><em>o</em><em>n</em><em> </em><em>(</em><em>c</em><em>)</em><em> </em><em>+</em><em> </em><em>e</em><em>q</em><em>u</em><em>a</em><em>t</em><em>i</em><em>o</em><em>n</em><em> </em><em>(</em><em>b</em><em>)</em><em>:</em>
<em>
</em>
<em>T</em><em>h</em><em>e</em><em>n</em><em> </em><em>k</em><em>y</em><em> </em><em>:</em>
![{ \sf{2ky = 3 - 5}} \\ { \sf{ky = - 1}}](https://tex.z-dn.net/?f=%7B%20%5Csf%7B2ky%20%3D%203%20-%205%7D%7D%20%5C%5C%20%7B%20%5Csf%7Bky%20%3D%20%20-%201%7D%7D)
![{ \bf{y = \frac{1}{2} }} \\ { \sf{ky = - 1}} \\ { \sf{k = - 2}}](https://tex.z-dn.net/?f=%7B%20%5Cbf%7By%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20%7D%7D%20%5C%5C%20%7B%20%5Csf%7Bky%20%3D%20%20-%201%7D%7D%20%5C%5C%20%7B%20%5Csf%7Bk%20%3D%20%20-%202%7D%7D)
(X-3)^2+5=14
Step 1: simplify both sides of the equation
X^2-6x+14=14
Step 2: subtract 14 from both sides
X^2-6x+14-14=14-14
X^2-6x=0
For this equation: a=1, b=-6,c=0
1x^2+-6x+0=0
Step 3: Use quadratic formula with a=1, b=-6, c=0
The answer is x=6 or x=0